Implementasi Program Pengembangan Kompetensi Tenaga Kesehatan dalam Meningkatkan Kualitas Pelayanan di Rumah Sakit Graha Husada Bandar Lampung - Celia Fitriani; Agus Purnomo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the implementation of healthcare workforce competency development programs in improving service quality at Graha Husada Hospital, Bandar Lampung. The background of this study is based on the importance of improving human resource quality as a key factor in determining healthcare service quality and patient satisfaction. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and document review. The research informants consisted of the Hospital Director, Head of General Affairs and Human Resources, Head of Medical Services, one physician, and two patients. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results show that the implementation of competency development programs at Graha Husada Hospital has been carried out through various training activities and continuing professional education. However, program planning has not been fully based on a systematic Training Needs Analysis (TNA). Program implementation has also not been optimal due to limited training budgets, high workload of healthcare workers, and insufficient post-training monitoring and evaluation. The competency development program has a positive impact on improving service quality, particularly in the dimensions of reliability and assurance. However, improvements in responsiveness and empathy have not been optimally perceived by patients. Therefore, more structured, sustainable, and balanced competency development programs focusing on both technical skills and service behavior are required in order to comprehensively improve hospital service quality.